INVENTARISASI SPESIES BINTANG MENGULAR (Ophiuroidea) DI PANTAI BILIK, TAMAN NASIONAL BALURAN, JAWA TIMUR - Rendy Setiawan; Fresha Aflahul Ula; Santi Feronika Sijabat (Department of Marine Sciences, Trunojoyo University of Madura, Indonesia, 2019)
ABSTRACT The Brittle stars is a member of the Phylum Echinodermata that lives in habitats in the intertidal, subtidal, and deep sea zones. Brittle stars can be found in areas of coral reefs, sand, seagrass, macroalgae (seaweed), and dead coral fragments. One of the many intertidal areas of the habitat is in the Baluran National Park Bilik Beach. Ophiuroidea is important to be studied in the conservation area, Baluran National Park, because it is a natural conservation area that has native ecosystems and is managed with a zoning system and utilized for natural tourism, research, science and education purposes. This study aims to determine the type of brittle stars found on the Baluran National Park. The method used in this research is descriptive method with road sampling technique in the Bilik Beach area. The brittle stars species found and described are 8 species, namely Ophiomastix annulosa, Ophiocoma scolopendrina, Ophiocoma brevipes, Ophioplocus imbricatus, Ophiolepis cardioplax, Ophiolepis superba, Ophiarachna parvispina, and Macrophiothrix longipeda. Keywords: Baluran National Park, Brittle stars.ABSTRAKBintang mengular merupakan anggota dari filum Echinodermata yang hidup pada habitat di zona intertidal, subtidal, dan laut dalam. Bintang mengular dapat ditemukan di area terumbu karang, pasir, lamun (seagrass), makroalga (seaweed), dan pecahan karang mati. Salah satu wilayah intertidal yang banyak terdapat habitat tersebut adalah di Pantai Bilik Taman Nasional Baluran. Ophiuroidea menjadi penting untuk dikaji di area konservasi yaitu Taman Nasional Baluran, karena merupakan kawasan pelestarian alam yang mempunyai ekosistem asli dan dikelola dengan sistem zonasi serta dimanfaatkan untuk tujuan pariwisata alam, penelitian, ilmu pengetahuan, dan pendidikan. Penelitian ini bertujuan untuk mengetahui jenis bintang mengular yang terdapat di Pantai TN Baluran. Metode yang digunakan dalam penelitian ini adalah metode deskriptif dengan teknik road sampling di area Pantai Bilik. Spesies bintang mengular yang ditemukan dan dideskripsikan sebanyak 8 spesies, yaitu Ophiomastix annulosa, Ophiocoma scolopendrina, Ophiocoma brevipes, Ophioplocus imbricatus, Ophiolepis cardioplax, Ophiolepis superba, Ophiarachna parvispina, dan Macrophiothrix longipeda.Kata Kunci: Bintang mengular, Taman Nasional Baluran